179k views
14 votes
Find the inverse of y=ln2x

User Skryvets
by
5.1k points

1 Answer

4 votes

Answer:

The exponential function, exp : R → (0,∞), is the inverse of the natural logarithm, that is, exp(x) = y ⇔ x = ln(y). Remark: Since ln(1) = 0, then exp(0) = 1. Since ln(e) = 1, then exp(1) = e.

Step-by-step explanation:The exponential function, exp : R → (0,∞), is the inverse of the natural logarithm, that is, exp(x) = y ⇔ x = ln(y). Remark: Since ln(1) = 0, then exp(0) = 1. Since ln(e) = 1, then exp(1) = e.

User Jason Snelders
by
5.1k points